Healthcare providers' attitudes towards care for men who have sex with men (MSM) in Malawi - Lester Kapanda; Vincent Jumbe; Chimaraoke Izugbara; Adamson S. Muula (BMC, 2019)
Abstract Background Men who have sex with men (MSM) are a priority group in Malawi's national response to Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS). There are limited data on service providers' acceptability to deliver appropriate sexual health services in relation to HIV prevention, care and treatment targeting the MSM. We assessed attitudes of healthcare providers already working, health professions students and faculty at health professions training institutions regarding the provision of MSM focused HIV related health services. Methods We conducted a qualitative study between April and May 2017 in Lilongwe, Malawi. We purposively recruited 15 participants (5 health service providers, 5 health professions students and 5 faculty of tertiary health training institutions) among whom individual in-depth interviews were conducted. Interviews were audio recorded, transcribed and analysed thematically. Results Participants recognized MSM as having health needs and rights. Participants generally expressed willingness to deliver appropriate healthcare because they perceived this as their professional responsibility. Participants suggested that it was the responsibility for MSM to disclose their sexual orientation and or preferences when they access care such that healthcare providers better anticipate their care needs. They suggested a need to increase the availability of MSM-centered and friendly health services as well as trained providers that are non-judgmental, non-discriminatory and have respect for people's right to health care access. Conclusion Despite widespread poor attitudes against MSM in Malawi, health service providers and health professions students and faculty accepted and were willing to provide MSM-focused health services. The acceptability and willingness of health service providers, health professions students and faculty to provide health services to MSM offer hope and scope for efforts to strengthen the delivery of health services and quality of care to MSM in Malawi.